Native fruits of Peru as a potential source of nutrients, bioactive compounds and antioxidant capacity in the nutritional requirements of vulnerable groups - Obregón La Rosa, Antonio José; Talledo Rodríguez, Garbiña Anadeira; Pinedo Taco, Rember Emilio (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2021)
The Andean region has a great variety of native species, which can satisfy a large part of the daily nutritional requirements, necessary for vulnerable populations, due to their high nutrient content. In this work, the physicochemical characterization of three types of native fruits from the Andean region of Peru was carried out: Aguaymanto (Physalis peruviana), yellow pitahaya (Selenericeus megalanthus) and Quito (Solanum quitoense), the potential of nutrients, the bioactive compounds, antioxidant capacity and was compared with the nutritional requirement of vulnerable groups (older adults, pregnant mothers and lactating mothers). For each vulnerable group, the average contribution of the fruits and the theoretical average contribution of a five-day diet were contrasted with the IDR10, which represents 10 % of the total requirement of the Dietary Reference Intake (IDR) considering that the consumption of the fruit represents 10 % of the total food intake per day. To test the hypothesis, a global index was determined as a function of desirability, determined from the geometric mean of the indices of physical-chemical, nutritional, bioactive compounds and antioxidant capacity of the studied fruits. The non-parametric statistical method of Kruskal Wallis was used with a significant level of 5 %, significantly verifying (p≤ 0.05) that the content of the components of the native fruits represent a potential source of nutrients, bioactive compounds and antioxidant capacity in the nutritional requirements of vulnerable groups.